Inhibitory and excitatory conditioned cues associated with alcohol differentially modulate the nucleus accumbens shell: involvement of 5-HT7 receptors - Hauser, Sheketha R.; Deehan, Gerald A.; Knight, Christopher P.; Waeiss, Robert A.; Engleman, Eric A.; Johnson, Phillip L.; McBride, William J.; Bell, Richard L.; Truitt, William A.; Rodd, Zachary A. (Frontiers in Psychiatry, 2025)
IntroductionThe ability of conditioned cues to evoke drug craving is considered a critical factor precipitating relapse of drug use. The nucleus accumbens shell (AcbSh) is a structure that mediates drug-seeking via the influence of associations formed between conditioned cues and drug reward. MethodsIn the present experiments, alcohol-preferring (P) rats were exposed to three conditioned odor cues; CS+ associated with alcohol self-administration, CS− associated with the absence of alcohol (extinction training), and a neutral stimulus (CS0) presented in neutral environment with no association to alcohol. The experiments examined the effects of the conditioned cues on extracellular levels of dopamine (DA), serotonin (5-HT), and glutamate (GLU), as well as the pattern of activation of D1 receptor-containing neurons in the AcbSh. The involvement of 5-HT7 receptors within the AcbSh in regulating context- and cue-induced alcohol-seeking was also determined. ResultsPresentation of the CS+ resulted in increased extracellular DA levels and reduced 5-HT levels in the AcbSh, as well as increased activation of D1 receptor-containing neurons. In contrast, presentation of the CS− decreased extracellular DA and GLU levels in the AcbSh. The conditioned cues did not affect DA levels in the Acb core. The intra-AcbSh administration of a 5-HT7 antagonist enhanced context- and cue-induced alcohol seeking, whereas a 5-HT7 agonist reduced these behaviors. DiscussionOverall, the data suggest that there are distinct neurocircuits within the AcbSh that mediating the effects of excitatory and inhibitory conditioned cues on motivated behavior. While this work highlights a complex interaction of several neurotransmitter systems, it may also suggest a potential role for behavioral therapies involving extinction training and 5-HT7 receptor activation as potential targets for the treatment of cue-induced drug-seeking behavior.